Final Report: Responsible Innovation and Scaling Consultancy - Altshul, Helen J. (CGIAR System Organization, 2025)
This final report summarizes the consultancy commissioned by the PPUto embed responsible innovation and scaling principles in its frameworks and operations. It consolidates findings from four deliverables, distils key lessons, and outlines recommendations and next steps for phased institutionalization and sustained learning across the CGIAR system.